Restoration of Blood Flow to the Proximal Femoral Epiphysis in Unstable Slipped Capital Femoral Epiphysis by Modified Dunn Procedure: A Preliminary Angiographic and Intracranial Pressure Monitoring Study. Issue 2 (February 2018) - Jackson, J. Benjamin; Frick, Steven L.; Brighton, Brian K.; Broadwell, Scott R.; Wang, Eric A.; Casey, Virginia F.
Abstract : Background: The major complication of unstable slipped capital femoral epiphysis (SCFE) is avascular necrosis (AVN) of the femoral head. The purpose of this study was to document by angiography the preoperative and postoperative perfusion to the proximal femoral epiphysis following an unstable SCFE. A specific aim was to determine whether blood flow could be restored. A secondary aim was to determine the efficacy of an intracranial pressure (ICP) monitor to assess blood flow within the femoral head intraoperatively. Methods: Nine patients with an unstable SCFE underwent superselective angiogram of the medial circumflex femoral artery preoperatively, followed by operative fixation with an open reduction using a modified Dunn approach. Femoral head blood flow was evaluated with an ICP monitor. Angiography was repeated postoperatively. Patients were followed radiographically to assess for AVN. Results: Follow-up averaged 22 months. Six patients did not have arterial flow to the femoral head on the preoperative angiogram. Flow was restored postoperatively on angiogram in 4 of the 6 patients. Two patients developed AVN. One had no flow to the femoral head preoperatively or postoperatively on angiogram and complete tearing of the periosteum was noted. In 1 patient, there was no ICP waveform after the initial reduction. After removing more callous and repeating reduction, the waveform returned. Of the 2 patients with AVN, 1 had an ICP waveform after reduction. Conclusions: This study documents that some patients with unstable SCFE present with reduced femoral head blood supply due to SCFE. It also demonstrates blood flow restoration in 4 patients by angiogram and 5 by ICP monitor after surgical treatment. No patient immediately lost blood flow due to surgery. ICP monitor is a safe intraoperative tool for real-time assessment of femoral head blood flow during open reduction of unstable SCFE. Presence of flow by ICP is not a guarantee that AVN will not develop, but absence of flow was predictive of AVN. Level of Evidence: Therapeutic level I—prognostic. See Instructions for Authors for a complete description of levels of evidence.